PENYULUHAN TENTANG PROSEDUR PENGURUSAN PERALIHANHAK ATAS TANAH KARENA PERBUATAN HUKUM - Arif Darmawan (Asian Journal of Innovation and Entrepreneurship, 2014)
DusunBendo,Gumukvillage,DistrictPakis, Magelang, Central.Mostly livelihoodsof the people are farmers. In addition to work as farmers, although there are somepeople who work as entrepreneurs. From the point of view of social interaction, thevillagersof Dusun Bendoa strong community of people who will sense of family, a senseof cooperation and solidarity.Life 'communityBendoThat still very simple and still adheres to the principle offamily of high impact as well in community awareness about the lack of publicunderstanding of the importance of the maintenance of transitional land rights thatwalking is not in accordance with applicable law, especially positive law .